Physicochemical properties of banana peel powder in functional food products - Mohd Dom, Zanariah; Mujianto, Lisnurjannah; Azhar, Adibah Zahiah; Masaudin, Saidatul Nurul Atika; Samsudin, Rosnah (Rynnye Lyan Resources, 2021)
Saba banana is one of the most favourite banana varieties in Malaysia. It also generates a concerning amount of waste as the only value part is the pulp. Banana peel has been proven to have a lot of nutritional content that should not be ignored and wasted. Conversion of banana peel to powder will convert it into a value-added product in the food industry. Preliminary study on the protein, moisture, crude fibre and fat was carried out for 2 different stages of maturity which are stage 2 (light green) and stage 5 (yellow with green tips). Both stages have almost similar proximate analysis values and hence stage 2 of banana was chosen for the next analysis, due to the high waste of banana peel in stage 2 in SME (Small Medium Enterprise) in the production of banana chips. This study characterized the banana peel powder for storage application at different sizes of particles which are 1-125 µm, 126-250 µm and >250 µm. As the particles of the banana peel powder increases, the flowability of the powder decreases. It was found that green banana peel (stage 2) at sample A (1-125 µm) has the highest true density, but sample C (>250 µm) has the highest bulk density. The pH mean value of the three sizes also ranges from 6.15 to 6.46. The powder’s pH (6.15-6.46) is in the standard wheat flour acidity range. Moreover, the study on the water holding capacity at different temperatures identifies that banana peel powder has a high water holding capacity ranging from 3.83 to 6.45 g water/g dry sample. In short, this study is a success in identifying the potential of banana peel powder in food products based on its characteristics.